Biosynthesis of tetrahydrofuran lignans in Virola surinamensis (Revista Brasileira de Ciências Farmacêuticas, 2004)
The labelled substrates phenylalanine and phenylpropanoid E-isoeugenol were incorporated to 5-methoxy-4-O-methyl-E-isoeugenol (E-isoelemicin) and to the tetrahydrofuran lignan verrucosin in plantlets of Virola surinamensis (Myristicaceae).